PENGARUH LAMA WAKTU ULTRASONIKASI TERHADAP KONDUKTIVITAS LISTRIK GRAPHENE - La Agusu; Yuliana Yuliana; Yustin Biringgalo; Risal Day; Herdianto Herdianto (Jurnal Aplikasi Fisika, 2017)
Research on the effect of ultrasound time on graphene electrical conductivity has been conducted. The purpose of this research is to analyze the best ultrasonication time to synthesize graphene material with high electrical conductivity value. Graphene is synthesized by a graphite oxide reduction method. Graphite is oxidized to form graphite oxide by modifying the Hummer method. Graphite oxide was diultrasonikasi with variation of time 60, 90, 120, 150, and 180 minutes with frequency 53KHz. Then the graphite oxide reduction process was chemically done with the addition of Zn 1,6 gram powder and hydrothermal technique using microwave resistance of 70% for 30 minutes. Analysis of the graphene oxide structure was done by XRD testing and electrical testing of graphene oxide using four probes (FPP). The test results show that graphene with 180 minutes of ultrasonication time has the best electrical conductivity of 0.6512 S / cm.   Keywords: Graphite, ultrasonication, electrical conductivity, graphene oxide.